2016
DOI: 10.1002/pmic.201500284
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free analysis of human cerebrospinal fluid addressing various normalization strategies and revealing protein groups affected by multiple sclerosis

Abstract: The aims of the study were to: (i) identify differentially regulated proteins in cerebrospinal fluid (CSF) between multiple sclerosis (MS) patients and non-MS controls; (ii) examine the effect of matching the CSF samples on either total protein amount or volume, and compare four protein normalization strategies for CSF protein quantification. CSF from MS patients (n = 37) and controls (n = 64), consisting of other noninflammatory neurological diseases (n = 50) and non neurological spinal anesthetic subjects (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Such a protein has yet to be described in tears. A publication of cerebral spinal fluid proteomics indicates that the preferable way to quantify proteins is to first match the samples on total protein amount and then normalize the data based on the median intensities [463]. This technique has yet to be used in tear film biochemistry studies.…”
Section: Biochemical Properties Of Tearsmentioning
confidence: 99%
“…Such a protein has yet to be described in tears. A publication of cerebral spinal fluid proteomics indicates that the preferable way to quantify proteins is to first match the samples on total protein amount and then normalize the data based on the median intensities [463]. This technique has yet to be used in tear film biochemistry studies.…”
Section: Biochemical Properties Of Tearsmentioning
confidence: 99%
“…12 To verify the reproducibility and consistency of the results, all samples were run in duplicate in the same and in 2 consecutive experiments. According to previously published procedures, 15 for each examined patient, the CSF level of each protein was normalized to the total protein concentration of each CSF sample (measured by the Bradford protocol). However, analyses results were unchanged when experiments were also run using absolute concentrations of CSF protein.…”
Section: Study Populationmentioning
confidence: 99%
“… 14 It is upregulated in numerous chronic inflammatory conditions and is expressed by several cells, including microglia, macrophages, and astrocytes. 14 In proteomic studies, 15 , 16 CHI3L1 has been identified as a potential biomarker for MS, and CHI3L1 levels in CSF have been proposed as a prognostic marker for conversion from CIS to MS. 8 , 14 , 17 …”
mentioning
confidence: 99%